Testing the boundaries self, faith, interpretation and changing trends in religious studies - 'Iolana, Patricia; Tongue, Samuel (Cambridge Scholars Publishing, 2011)
As individual members of various faith traditions within contemporary society we have the ability (although not always the opportunity) to create our own paradigmatic image of the Divine; moreover, as a society we can alter, transform, or even replace tho
Keywords: Religion : Congresses; Religions : Congresses